The SPaCE diagnostic: a pilot study to test the accuracy of a novel point of care sensor for point of care detection of burn wound infection. Issue 4 (December 2020) - Young, A.E.; Thet, N.T.; Mercer-Chalmers, J.; Greenwood, R.J.; Coy, K.; Booth, S.; Sack, A.; Jenkins, A.T.A.
Summary: Background: Wound infection in burn patients is common and has an impact on outcomes. There is no objective method to diagnose infection at point of care (PoC). Early diagnosis prevents progression to sepsis. Diagnostic subjectivity supports over-diagnosis, unnecessary hospitalization, and antibiotic overuse. Aim: This pilot study aimed to investigate the accuracy of a novel PoC wound infection diagnostic in burn patients. Methods: We produced, and in vitro tested, a PoC diagnostic for early wound infection diagnosis. The prototype SPaCE diagnostic uses a patented lipid vesicle suspension into which a clinical swab is placed. The diagnostic delivers a colour-response to Staphylococcus aureus, Pseudomonas aeruginosa, Candida species and Enterococcus faecalis at toxin release. A pilot clinical diagnostic accuracy study was undertaken. The reference standard was a retrospective decision made by an expert clinical panel using routinely available data. Findings: Data was available from 33 of 34 patients. Of these, 52% were considered to have a wound infection, 42% not, and two (6%) were equivocal. The diagnostic results showed 24% were infected, 42% were not and 33% produced intermediate results. Agreement between clinical judgement and diagnostic result, assessed using a weighted Kappa, was 0.591 suggesting moderate agreement. If the intermediate results were excluded, 22 sets of data with definitive results achieved a Kappa statistic of 0.81 suggesting 'almost perfect' agreement. Sensitivity and specificity were 57% (8/14) and 71% (12/17), respectively. Conclusion: This pilot study provided evidence that the SPaCE diagnostic could provide valuable and timely data to support clinical decision-making at PoC for wound infection.